2018
DOI: 10.1002/jper.18-0366
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature plasma on peri‐implant–related biofilm and gingival tissue

Abstract: Background Evaluate the effect of low‐temperature plasma (LTP) on an anaerobic biofilm and on the biological response of an in vitro reconstituted gingival epithelium tissue. Methods Porphyromonas gingivalis W83 biofilm was cultured on titanium discs and reconstituted gingival tissues were submitted to similar treatment conditions. Treatments: LTP1—plasma treatment for 1 minute, LTP3—plasma treatment for 3 minute, CHX—0.2% chlorhexidine for 1 minute, GAS—gas only (no plasma) for 3 minute, and NEGATIVE—no treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 38 publications
(98 reference statements)
0
28
0
Order By: Relevance
“…However, they did not suggest a proper treatment time for P. gingivalis . Carreiro et al [18] applied an Ar-APPJ to an SLA surface for 1 and 3 minutes and reported a reduction in P. gingivalis colonization. However, the plasma treatment was ineffective compared to Chlorhexidine irrigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they did not suggest a proper treatment time for P. gingivalis . Carreiro et al [18] applied an Ar-APPJ to an SLA surface for 1 and 3 minutes and reported a reduction in P. gingivalis colonization. However, the plasma treatment was ineffective compared to Chlorhexidine irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…For implant treatment, Koban et al [17] applied an APPJ to machined titanium discs contaminated by Streptococcus mutans or multiple species from human saliva and observed a superior antiseptic effect of the APPJ compared to that of Chlorhexidine rinse. Recently, Carreiro et al [18] evaluated an Ar gas–based APPJ treatment on sandblasted and acid-etched (SLA) surfaces, which are among the most widely used surfaces of currently available commercial dental implants. They showed the possibility of using APPJs on SLA surfaces as a decontamination method for P. gingivalis biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…However, the antibacterial effects of LTP, which are intermediated by ROS, do not show to increase bacterial resistance when bacteria are continuously exposed to it. These findings indicate that LTP is potentially a good candidate for in vivo antibiotic treatments [12][13][14].…”
Section: Introductionmentioning
confidence: 72%
“…Thus, LTP is potentially an effective treatment aiming to reduce P. gingivalis biofilm on implant surfaces and is safe for the gingival epithelium. Additionally, it may be related to cell repair [13].…”
Section: Surface Modification and Osseointegrationmentioning
confidence: 99%
See 1 more Smart Citation